Gabon: Strengthening the Transport Sector - Mohan, P.C. (World Bank, Washington, DC, 2012)
The project -Transport Sector Technical Assistance, later renamed Project for the Adjustment and Planning of the Urban and Transport Sectors - was conceived as an integral part of the government's overall macroeconomic strategy following the adjustment of the CFA franc. This strategy focused on reducing, rationalizing and improving the efficiency of the private sector, while promoting privatization and increasing competitiveness in the economy. In addition to supporting the government's macroeconomic policies, the project aimed to strengthen a broad range of capacities in the urban and transport sectors by encouraging the wide participation of government, public sector entities, the private sector and the international donor community in setting the sector strategies.